2021
DOI: 10.3390/v13091829
|View full text |Cite
|
Sign up to set email alerts
|

The Innate Immune DNA Sensing cGAS-STING Signaling Pathway Mediates Anti-PRRSV Function

Abstract: Porcine reproductive and respiratory syndrome virus (PRRSV) modulates host innate immunity which plays a key role against PRRSV infection. As a RNA virus, PRRSV is mainly sensed by innate immune RNA receptors, whereas the role of innate immune DNA sensors in the PRRSV infection has not been elucidated. Here, we investigated the roles of DNA sensing cGAS-STING pathway in both PRRSV infected Marc-145 cells and porcine macrophages. The results show that in Marc-145 cells, the stable expression of STING with or wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…Our study demonstrated that the cGAS is important in inhibiting PRRSV replication, consistent with previous studies ( 28 ). Their study suggested that cGAS and STING possess the anti-PRRSV effect.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study demonstrated that the cGAS is important in inhibiting PRRSV replication, consistent with previous studies ( 28 ). Their study suggested that cGAS and STING possess the anti-PRRSV effect.…”
Section: Discussionsupporting
confidence: 93%
“…Their study suggested that cGAS and STING possess the anti-PRRSV effect. Nevertheless, the mechanism is unclear ( 28 ). Our findings show that cGAS overexpression promotes IFN-β production during PRRSV infection at both the transcription and translation levels ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the porcine STING siRNA were synthesized based on our previous study (28). One day before transfection, 3D4/21 cells were plated into 24-well plates and cultured in growth medium.…”
Section: Asfv Infection and Sirna Treatmentmentioning
confidence: 99%
“…Porcine alveolar macrophages (3D4/21, ATCC CRL-2843) were grown in RPMI 1640 (Hyclone Laboratories, Logan, UT, USA) supplemented with 10% FBS with 1% penicillin-streptomycin solution, and maintained at 37 °C with 5% CO2 in a humidified incubator. The viruses including a DNA virus Herpes Simplex Virus 1 (HSV1-GFP) as well as RNA viruses Vesicular Stomatitis Virus (VSV-GFP) and Highly Pathogenic Porcine Reproductive and Respiratory Syndrome Viruses (HP-PRRSV XJ17-5-GFP and HP-PRRSV vaccine strain JXA1-R-GFP) were used as we previously reported [22][23][24].…”
Section: Cells and Virusesmentioning
confidence: 99%
“…Interestingly, recent publications have suggested the relevance of the cGAS-STING pathway in the process of RNA virus infections [19][20][21][22]. However, whether Mn 2+ plays a role in the cGAS-STING pathway mediated anti-RNA virus infections is still largely unclear.…”
Section: Introductionmentioning
confidence: 99%